Evaluation of data sharing in production firms and innovation orientation in the effect of management capability on operational performance - Çeltekligil, Kudret; Adıgüzel, Zafer (Elsevier, 2019)
The aim of this study is to investigate and analyze the effects of information sharing on the operational performance of technology companies in the competitive environment in the management skills and innovative focus of the firms in the technology sector. Due to the limitations of the research, only the technology firms formed our sample group and we can give the analysis results only through the technology companies. The sample population of the research should also be considered in terms of the intensive technology-oriented industrial firms. A research model has been developed to examine the relationships between variables and to test hypotheses. The data obtained from the collected 312 questionnaires were responded by the engineers working in 28 technology companies. In particular, because of the fact that the sample population is engineers, they have taken part in our research because they assume important duties and responsibilities in both the operational part and in the innovation orientation. In conclusion, we have proved the advantage of sharing information and being innovative in order not to fall back from competition for technology companies.
Keywords: Management Capability; Intra-Organizational Knowledge Sharing; Innovation Orientation; Operational Performance